AKTIVITAS ANTIBAKTERI EKSTRAK DADANGKAK (Hydrolea spinosa) TERHADAP BAKTERI Bacillus subtilis, Staphylococcus aureus DAN Escherichia coli - Putri Vidiasari Darsono; M. Fajriannor T. M. (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2020)
Hydrolea spinosa are one of the plants that grow in swamp habitat. This plant is used by the loksado hill dayak community in the area Hulu Sungai Selatan as a cure for malaria, coughing up blood, medicine for sores and ulcers and mosquito repellent. The phytochemical content of H. spinosa leaves include tannins, steroids, flavonoids, and alkaloids. Bacillus subtilis, Staphylococcus aureus is gram positive bacteria while Escherichia coli is gram negative bacteria. This study aims to determine the Antibacterial Potential of Dadangkak Ethanol Extract (Hydrolea spinosa) Against Bacillus subtilis, Staphylococcus aureus, and Escherichia coli as local plants in South Kalimantan. The method used is disk diffusion, the stages of this research are starting from sample preparation, extraction, antibacterial screening, sterilization and media making, rejuvenation and making of bacterial suspensions, making variable concentration stock, and antibacterial test. Positive control using Amoxicillin 25 mcg and negative control using 20% ​​DMSO. Based on the results of the average inhibition zone of ethanol extract of dadangkak leaves on Bacillus subtilis with a concentration of 100 mg / ml, 300 mg / ml, 500mg / ml which is 4.3 mm, 4 mm, 5 mm, in Staphylococcus aureus with a concentration of 100 mg / ml, 300 mg / ml, 500mg / ml are 3mm, 4.6mm, 6.3mm while Escherichia coli with a concentration of 100 mg / ml, 300 mg / ml, 500mg / ml are 2.3mm, 3mm, 3.3mm. This shows that dadangkak leaf extract has antibacterial activity on gram-positive and gram-negative bacteria.